Sensorimotor control and neuromuscular activity of the shoulder in adolescent competitive swimmers with generalized joint hypermobility - Frydendal, T.; Eshøj, H.; Liaghat, B.; Edouard, P.; Søgaard, K.; Juul-Kristensen, B. (Gait and Posture, 2018)
Introduction: Shoulder pain is highly prevalent in competitive swimmers, and generalized joint hypermobility (GJH) is considered a risk factor. Sensorimotor control deficiencies and altered neuromuscular activation of the shoulder may represent underlying factors. Research question: To investigate whether competitive swimmers with GJH including shoulder hypermobility (GJHS) differ in shoulder sensorimotor control and muscle activity from those without GJH and no shoulder hypermobility (NGJH). Methods: Competitive swimmers (aged 13.17) were recruited. GJHS or NGJH status was determined using the Beighton score (0.9) and Rotes-Querol test (positive/negative). Inclusion criteria for GJHS were a Beighton score .5 and minimum one hypermobile shoulder, while NGJH was defined as a Beighton score .3 and no shoulder hypermobility. Three prone lying, upper-extremity weight-bearing shoulder stabilometric tests were performed on a force platform: Bilateral upper-extremity support eyes open (BL-EO) and eyes closed (BL-EC) and unilateral upper-extremity support eyes open (UL-EO). Surface electromyography (SEMG) was measured from the upper trapezius, lower trapezius, serratus anterior, infraspinatus and pectoralis major muscles. SEMG was normalized using maximal voluntary isometric contractions and presented relative to maximal voluntary SEMG (%MVE). Co-contraction index (CCI) was calculated for the following muscle pairs: upper trapezius-lower trapezius, upper trapezius-serratus anterior, and infraspinatus-pectoralis major. Between-group differences in stabilometric parameters, %MVE, and CCI were analyzed with a mixed effects model. Results: Thirty-eight swimmers were enrolled as GJHS (n=19) or NGJH (n=19). There were no group differences in stabilometric parameters or CCI. GJHS displayed significantly decreased (29%) pectoralis major activity during BL-EO compared to NGJH (5.35) 1.77%MVE vs. 7.51 ) 1.96%MVE; p=0.043). Significance: Adolescent competitive swimmers with GJHS displayed no shoulder sensorimotor control deficiencies and no generally altered shoulder muscle activity pattern, except for decreased pectoralis major activity in BL-EO. Longitudinal studies are needed to investigate whether decreased pectoralis major activation contributes to the development of shoulder pain in swimmers with GJHS.